Association between physical activity and episodic memory and the moderating effects of the apolipoprotein E ε4 allele and age - Lee, Boung Chul; Choe, Young Min; Suh, Guk-Hee; Choi, Ihn-Geun; Kim, Hyun Soo; Hwang, Jaeuk; Yi, Dahyun; Kim, Jee Wook (Frontiers in Aging Neuroscience, 2023)
Background: An abundance of evidence indicates that physical activity may protect against Alzheimer's disease (AD) and related cognitive decline. However, little is known about the association between physical activity and AD-related cognitive decline according to age and the apolipoprotein E (APOE) ε4 allele (APOE4) as major risk factors. Therefore, we examined whether age and APOE4 status modulate the effects of physical activity on episodic memory as AD-related cognition in non-demented older adults. Methods: We enrolled 196 adults aged between 65 and 90 years, with no dementia. All participants underwent comprehensive clinical assessments including physical activity evaluation and APOE genotyping. The AD-related cognitive domain was assessed by the episodic memory, as the earliest cognitive change in AD, and non-memory cognition for comparative purposes. Overall cognition was assessed by the total score (TS) of the Consortium to Establish a Registry for Alzheimer's Disease neuropsychological battery. Results: We found significant physical activity × age and physical activity × APOE4 interaction effects on episodic memory. Subgroup analyses indicated that an association between physical activity and increased episodic memory was apparent only in subjects aged > 70 years, and in APOE4-positive subjects.Our findings suggest that physical activity has beneficial effects on episodic memory, as an AD-related cognitive domain, in individuals aged > 70 years and in APOE4-positive individuals.Physical activity and episodic memory 4 Physicians should take age and APOE4 status account into when recommending physical activity to prevent AD-related cognitive decline.